Estudo da ligação viga-pilar em sistema estrutural de concreto considerando a variação da semi-rigidez por meio de parâmetros geométricos da ligação - Araújo, Tássio Jorge Figueiredo de (2018)
This work presents a study to quantify the influence of geometrical and stiffness parameters on the behavior of beam-column concrete connections. Therefore, linear elastic models are designed by using three-dimensional finite elements in the commercial software Abaqus. These models serve as a reference for the optimization of geometrical and rigidity parameters of reticulated models, which are commonly used in structural projects. The results confirm some tendencies of influence by parameters already reported in the literature, such as variations in stiffness caused by eccentricity and width variations. The results indicate variations in vertical displacement of the beams up to 5%, maintaining the vertical load and varying only the eccentricity and up to 60% only by varying the widths of the elements. Furthermore, the use of punctual representations of semi-rigidity on monolithic concrete connections through rotational springs is discarded, proving necessary an improvement of the model to represent the behavior of the connection. Several models have been proposed and tested in the representation of the semi-rigid behavior of the connections, making use of rigid core, rotational springs and variations of inertia and area.